Endometriosis as very common cause of chronic pelvic pain – overview of actual knowledge - Miszczyk, Karolina; Gonet, Malwina; Kania, Agata; Lazar, Michał; Maj, Patrycja; Maternia, Jakub; Mozer, Piotr; Sergiel, Natalia; Serwik-Trandasir, Aleksandra; Włodarczyk-Cybulska, Karolina (Journal of Education, Health and Sport, 2023)
Introduction and purpose of the study: Endometriosis is a prevalent condition that affects women in their reproductive years. Diagnosing the condition and determining its manifestations can be complex and uncertain, as they vary among individuals. The symptoms of endometriosis have a detrimental impact on the overall quality of life for patients, leading to decreased well-being, limitations in physical activity, and impaired social functioning. The available treatments for endometriosis are determined based on the primary symptom (chronic pelvic pain or infertility) and are primarily focused on surgical interventions, hormonal therapies, and analgesic medications. These treatments often come with numerous side effects and rarely offer long-term relief. In this review, we provide a comprehensive overview of the current knowledge regarding endometrosis, including its pathophysiology, diagnostic methods, and the existing treatment options. Materials and methods: The analysis relied on examining materials obtained from both the "PubMed" database and books. The search was performed using the keywords: "endometrosis diagnosis", "endometrosis therapy", "dysmenorrhea", "combined oral contraceptive", "laparoscopy". Summary: Endometriosis poses a significant health concern due to its correlation with compromised daily functioning and infertility. Appropriate diagnostic and therapeutic management of endometriosis contributes to a significant improvement in the wellbeing of patients, including a reduction in pain and improved ability to function both physically and socially. Conservative treatment consists of hormonal therapy, which regulates the menstrual cycle, reduces the severity of pain symptoms and inhibits the development of endometrial foci outside the uterus. In situations of advanced endometriosis, pharmacological treatments may not be sufficient and surgical therapy is required.